Analysis of the relationship between daylight illuminance and cognitive, affective and physiological changes in visual display terminal workers. (March 2020) - Öner, M; Kazanasmaz, T; Leccese, F; Salvadori, G
This study explored the impact of daylight illuminance on cognitive load during visual display terminal use by means of various physiological, performance and subjective measures. Repeated-measures design was adopted to identify the impact of variations in daylight levels that were manipulated through the shading system configurations (shading-on; shading-off). A total of 30 subjects performed visual and cognitive demanding tests. Performance measures were supported by subjective data and eye-related measures during the experimental analysis. Results revealed that the use of a shading system had positive impact on sustained attention. Concerning ocular measures, percentage of eye closure values showed opposite tendencies among vigilance and sustained attention demanding tests. Eye aspect ratio-max and blink duration were significantly correlated with reported glare sensation. In all tests, eye aspect ratio-max was found significantly higher in lower illuminances. Search velocity was significantly correlated with ocular variables in higher illuminances whereas sustained attention showed an opposite trend. This, initially, explains that even slight differences in daylight illuminance might have distinctive effects on the relationship between different groups of assessment variables while measuring cognitive load. Secondly, it proves the significance of carrying out sensitive experiments in terms of both light levels and test characteristics. Practical application: The findings of this study could suggest that a practical application, the use of a shading device, might deliver an efficient solution on such a multifaceted question about the potential effects of luminous environment on the evaluation of cognitive load. Work environments might be considered as cognitively efficient if only the harmony of less mental effort, more satisfaction and less health problems exist, which together ultimately deliver higher work performance. In real-world work environments, application of such shading devices involves advantages not only for avoiding excessive daylight exposure or optimizing energy consumption, but also facilitating cognitive, affective and physiological processes of individuals.